ANALISIS PERBEDAAN KINERJA KEUANGAN ANTARA PEMENANG DAN BUKAN PEMENANG INDONESIA SUSTAINABILITY REPORTING AWARDS - Sri Arthini, Ni Wayan; Sri Harta Mimba, Ni Putu (E-Jurnal Akuntansi, 2016)
Indonesia. Sustainability Reporting Awards (ISRA) was held to appreciate companies that have revealed sustainability report. T his study aims to determine whether there are differences in financial performance between the winn er and non winner of ISRA. This study uses secondary data . Data consist of financial statements of  companies listed in Indonesian Stock Exchange and gathered from National Center for Sustainability Reporting (NCSR). The sample consist of 21 companies that became the winner of ISRA and 22 companies that did not become winners in ISRA, with nonprobability sampling method. Data observed with Independent Sampel T-test and Mann Whitney U. This study concludes that there is no significant difference in financial performance between the winner and non winner of ISRA . Th is is  probably due for Indonesian case, winning ISRA is not yet become important information for stakeholders.
Keywords: Indonesia Sustainability Reporting Awards, financial performance, return on assets, return on equity, net profit margin